Project-Oriented Perceptions of Research, Development and Innovation in Hungarian, Polish and Romanian Enterprises - Dobos, Oszkar; Csiszarik-Kocsir, Agnes (Transformations In Business & Economics, 2025)
Research, development and innovation is the watchword and driving force of the 21st century. Research, development and innovation initiatives take the form of projects. However, projects are considered to be particularly risky because of the unpredictable outcomes and results of innovation. RDI activities are most likely to result in concrete, tangible improvements that are relevant to the economy as a whole. The most preferred innovation targets are embodied in processes, product developments, production systems, services, channels and networks. For an innovation initiative to succeed, it is essential to have management support that can be learned and developed. For all these reasons, it is very important that RDI activities have the background that can safely take an organisation to the achievement of results. Experience and organisational knowledge are very important for these projects. This kind of knowledge can often only be grasped from the project side, and the key in many cases lies in effective leadership and collaboration. The aim of our study is to investigate how Hungarian, Polish and Romanian SMEs relate to innovation and the background of innovation projects. Our aim is to assess the project and innovation awareness and orientation of these organisations in the light of the results of a primary research study covering three countries.